Plato and the poets - Destrée, Pierre.; Herrmann, Fritz-Gregor. (Mnemosyne, Supplements, 2011)
Plato's discussions of poetry and the poets stand at the cradle of Western literary criticism. Plato is, paradoxically, both the philosopher who cites, or alludes to, works of poetry more than any other, and the one who is at the same time the harshest critic of poetry. The nineteen essays presented here aim to offer various avenues to this paradox, and to illuminate the ways poetry and the poets are discussed by Plato throughout his writing career, from the Apology and the Ion to the Laws. As well as throwing new light on old topics, such as mimesis and poetic inspiration, the volume introduces fresh approaches to Plato's philosophy of poetry and literature.